The Transcription Unit Architecture of Streptomyces lividans TK24 - Lee, Yongjae; Lee, Namil; Jeong, Yujin; Hwang, Soonkyu; Kim, Woori; Cho, Suhyung; Palsson, Bernhard O.; Cho, Byung-Kwan (Frontiers in Microbiology, 2019)
Streptomyces lividans is an attractive host for production of heterologous proteins and secondary metabolites of other Streptomyces species. To fully harness the industrial potential of S. lividans, understanding its metabolism and genetic regulatory elements is essential. This study aimed to determine its transcription unit (TU) architecture and elucidate its diverse regulatory elements, including promoters, ribosome binding sites, 5-untranslated regions, and transcription terminators. Total 1,978 transcription start sites and 1,640 transcript 3-end positions were identified, which were integrated to determine 1,300 TUs, consistent with transcriptomic profiles. The conserved promoter sequences were found as 5-TANNNT and 5-TGAC, representing the −10 and −35 elements, respectively. Analysis of transcript 3-end positions revealed the presence of distinctive terminator sequences and the RNA stem structure responsible for the determination of the 3-boundary of a transcript. Functionally related genes are likely to be regulated simultaneously by using similar promoters and being transcribed as a poly-cistronic TU. Poly-cistronic TUs were further processed or alternatively transcribed into multiple TUs to fine-regulate individual genes in response to environmental conditions. The TU information and regulatory elements identified will serve as invaluable resources for understanding the complex regulatory mechanisms of S. lividans and to elevate its industrial potential.